2009
DOI: 10.3748/wjg.15.4794
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with proton pump inhibitor is associated with undesired weight gain

Abstract: AIM:To examine the effects of long-term proton pump inhibitor (PPI) therapy on body weight (BW) and body mass index (BMI) in patients with gastroesophageal reflux disease (GERD). METHODS:The subjects were 52 patients with GERD and 58 sex-and age-matched healthy controls. GERD patients were treated with PPI for a mean of 2.2 years (range, 0.8-5.7 years), and also advised on lifestyle modifications (e.g. selective diet, weight management). BW, BMI and other parameters were measured at baseline and end of study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
1
18
1
1
Order By: Relevance
“…In addition, the family Erysipelotrichaceae that was found to be increased following PPI treatment have been associated with diet‐induced obesity in mouse models (Fleissner et al ., ), including mice with a humanized microbiota (Turnbaugh et al ., ). While long‐term PPI use has been recently associated with weight gain (Yoshikawa et al ., ), the increase of Erysipelotrichaceae that we observed after a relatively short treatment period may be caused by changes in nutritional habits, following the relief of symptoms by the PPIs. While we did not have nutritional data of these patients, pretreatment and post‐treatment, correlating microbial changes with dietary modifications will present an important follow up.…”
Section: Resultsmentioning
confidence: 69%
“…In addition, the family Erysipelotrichaceae that was found to be increased following PPI treatment have been associated with diet‐induced obesity in mouse models (Fleissner et al ., ), including mice with a humanized microbiota (Turnbaugh et al ., ). While long‐term PPI use has been recently associated with weight gain (Yoshikawa et al ., ), the increase of Erysipelotrichaceae that we observed after a relatively short treatment period may be caused by changes in nutritional habits, following the relief of symptoms by the PPIs. While we did not have nutritional data of these patients, pretreatment and post‐treatment, correlating microbial changes with dietary modifications will present an important follow up.…”
Section: Resultsmentioning
confidence: 69%
“…Emerging data suggest differences in the gut microbiota between lean and obese individuals play a role in obesity and are not a mere consequence of obesity. PPI use has been associated with weight gain in a nonsurgical patient population [8], a decrease in distal small intestinal pH [13], and small intestinal bacterial overgrowth [14]. Multiple studies have shown that obese individuals have a higher relative abundance of bacteria from the phylum Firmicutes and a lower relative abundance from the phylum Bacteroidetes compared with lean individuals [15,16].…”
Section: Discussionmentioning
confidence: 98%
“…There is a high rate of proton pump inhibitor (PPI) and histamine-2 blocker (H2 B) use in severely obese patients for chronic gastroesophageal reflux disease (GERD) before LRYGB [6,7]. PPI use has also been associated with undesirable weight gain [8]. However, there is no published data on the effect of PPI or H2 B use leading up to LRYGB and weight loss after LRYGB.…”
mentioning
confidence: 98%
“…20 On the contrary, long-term treatment of PPI is rather associated in general trend with mass gain in patients with gastro-oesophagus reflux disease. 21 Subsequently, the PPI intake was stopped in the beginning of the 2 nd half-year after which the eructation symptoms were diminished. Figure 5 shows the changes in the BMI and energy requirement over one year under the 2 diet programs.…”
Section: Gluten and Egg Free-based Foodsmentioning
confidence: 99%
“…During the 2 successive diet plans, all observations were daily recorded, and body data were weekly home-monitored. The success of such approaches was shown by the diminution of the crisis frequency, BMI drop to normal values (20)(21)(22)(23)(24)(25), body mass stability as well as hiatal hernia disappearance.…”
Section: Introductionmentioning
confidence: 99%